Cloning of cDNA Encoding GRA1 Protein of Tachyzoite Toxoplasma Gondii Local Isolate - Erma Sulistyaningsih; Sukarti Moeljopawiro; Jarot Subandono; Wayan T. Artama (Universitas Gadjah Mada, 2005)
Gene encoding GRA1 protein is potent DNA-vaccine candidate against toxoplasmosis. The aim of the research was to clone the gene encoding GRA1 protein of tachyzoite Toxoplasma gondii local isolate by DNA recombinant technology. Tachyzoite was grown in Balb/c mice in vivo. Messenger RNA was isolated from total RNA and it was used to synthesis cDNA. Complementary DNA encoding GRA1 protein of tachyzoite Toxoplasma gondii local isolate was amplified and cloned in a prokaryote cloning vector. The recombinant GRA1-encoding gene was then digesting using EcoRI restriction endonuclease and sequencing. The result showed that the recombinant GRA1- encoding gene consisted of DNA sequences encoding all signal peptide and mature peptide of GRA1 protein. Alignment of recombinant GRA1 sequence to gene encoding GRA1 protein of Toxoplasma gondii RH isolate showed 100% homologous.